The Influence of Intrinsic Motivation and Transformational Leadership on Student Association Performance at Institut Elkatarie: The Moderating Role of Islamic Work Ethics - Azim, Irfan; Baini, Nirmala; Amin, M. Zulkifli; Supriyanto, supriyanto (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
The primary goal of management in any organization is to achieve and maintain good performance to meet organizational objectives, which is essential for competitiveness in the global market. This study investigates how intrinsic motivation and transformational leadership influence the performance of the student council at the Institut Elkatarie, with Islamic work ethics as a moderating variable. Using quantitative methods and simple random sampling, data were collected from 90 out of 116 student council members for the 2023-2024 period and analyzed using regression analysis with IBM SPSS Statistics 25.0 The study shows that intrinsic motivation (X1) and transformational leadership (X2) both positively influence performance (Y), with significant T-values of 2.216 and 7.545, respectively. This suggests that enhancing intrinsic motivation and adopting transformational leadership can improve performance. However, the interactions between intrinsic motivation and Islamic work ethics (M), and transformational leadership and Islamic work ethics, were not significant, with significance levels of 0.294 and 0.571, respectively. This indicates that Islamic work ethics may not moderate the relationship between motivation, leadership, and performance in this context.